Depeche fra St. Petersborg. Omkring det åbne brev af 9. juli 1846 - Møller, Anders Monrad (Historisk Tidsskrift, 2013)
Dispatch from St. Petersburg On the King’s Open Letter dated 9 July 1846In 1839, Christian Frederik, born 1786, followed his cousin Frederik 6 as king of Denmark – including the dependencies Iceland, the Faroe Islands and Greenland – and as duke of the three duchies Schleswig, Holstein and Lauenburg. The new king, Christian 8, rightly doubted that his son and follower, Frederik, born 1808, king as Frederik 7 from 1848 to 1863, would have any offspring. This represented a latent problem, soon to become manifest. The order of succession was since 1665 laid down in the constitutional law, Lex Regia. It stated that if a king was without a son and heir, the next in the order of succession was the male offspring of his nearest female relation on the paternal side. The meaning and validity of this rule was undisputed as far as the Kingdom of Denmark was concerned, but for the duchy of Schleswig Christian August, duke of Schleswig-Holstein-Sonderburg-Augustenburg, asserted his own right of inheritance, based on the premise of strictly agnatic succession. Christian 8 appointed a commission to examine the problem of succession taken as a whole. Its report of 1846 was followed by the King’s personal announcement of July 8, the so-called aabne Brev (open letter), to the effect that Schleswig without any doubt followed the rules of the Kingdom, whereas there might be problems concerning some parts of the duchy of Holstein. Historians such as H.P. Giessing (1852), Alex. Thorsøe (1879), A.D. Jørgensen (1896-98), Georg Nørregård (1974), Viggo Sjøqvist (1984), Vagn Skovgaard-Petersen (1985), Claus Bjørn (1990), Lars Roar Langsleth (1998) and again Claus Bjørn (2003) have all censured Christian 8, albeit on different accounts. Some found the king too vacillating in his attitude and deemed his intervention a source of conflict. It is a fact though, that the King after 1846 became rather more popular in Denmark than he had been previously. Others have emphasized the strong commotion that was aroused not only in Holstein, but also in all other German states as well as in the Bundestag in Frankfurt am Main. However, the outrage here was an expression of general German nationalism more than a well-informed political attitude towards the problems in Schleswig. A third round of criticism claims that the King’s initiative was clumsy and served to demonstrate the impotence of absolute monarchy. Finally, it has been noted that he needed guarantees from the great powers of Europe, but utterly failed in securing them. No one ever bothered to throw some light on the behaviour and mood of the King during the days when he received the diplomatic reactions from the different European powers. An aide-de-camp, the naval officer C.C. Zahrtmann, who accompanied the King on his vacation on the island of Föhr in Schleswig, provides – by letters to his wife – important information on this matter. On August 27, Christian 8 received a copy of a dispatch from Nesselrode, the Russian minister of Foreign Affairs, sent to the Russian embassy in Copenhagen. In one of his letters, Zahrtmann told his wife that the king was exhilarated and filled with enthusiasm after reading it. In approval of the announcement of July 8, Russia concluded that everything would depend on upcoming negotiations; the government in Copenhagen ought to take preliminary measures to initiate such talks, as this would be the proper procedure. One can easily imagine the joy of Christian 8 who reacted by writing a letter to Czar Nicolai, proposing to send his own foreign minister to St. Petersburg for consultations. However, when receiving the answer at the beginning of the following month, he learned with disappointment, that Russia after all did not find the moment opportune for an intervention, as it would provoke uproar in the German nations. The explanation of this altered attitude is that in fact, neither the Russian czar nor the Danish king was able to predict the vehement German reactions carried forth under the influence of strong sentiments. Apart from this random sequence of events, Christian 8 was very near succeeding in 1846. Had he acquired the proper guarantees, the First Schleswig War, 1848-50, might never have taken place, and neither had perhaps the Second War of 1864. It is difficult not to regret this lack of Russian firmness in the early autumn of 1846.